1998
DOI: 10.1038/sj.onc.1201820
|View full text |Cite
|
Sign up to set email alerts
|

Absence of autophosphorylation site Y882 in the p185neu oncogene product correlates with a reduction of transforming potential

Abstract: Autophosphorylation of type I receptor tyrosine kinases (RTKs) comprises one step in the signaling events mediated by erbB receptors such as p185 neu and EGFR. Previous analysis of p185 neu has indicated that there are at least ®ve tyrosine autophosphorylation sites, Y882, Y1028, Y1143, Y1226/7 and Y1253, of which Y882 might be important because of its location in the kinase activity domain. We have speci®cally analysed the e ect of a Y882F (phenylalanine substituted for tyrosine at position 882) mutation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…Upon Tyr877 phosphorylation, the phosphoryl group establishes strong salt bridges with two arginine residues, which we suggest induces a conformational change in the A-loop, enabling it to attain the active conformation. Consistent with our observations, which were made with the human ErbB2 protein, Src dependence has also been observed for the constitutively active rat ErbB2/neu protein (39). Importantly, the amino acid sequence of the A-loop of rat ErbB2/neu is identical to that of human ErbB2, suggesting it may also undergo a conformational change when the corresponding Tyr882 is phosphorylated.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Upon Tyr877 phosphorylation, the phosphoryl group establishes strong salt bridges with two arginine residues, which we suggest induces a conformational change in the A-loop, enabling it to attain the active conformation. Consistent with our observations, which were made with the human ErbB2 protein, Src dependence has also been observed for the constitutively active rat ErbB2/neu protein (39). Importantly, the amino acid sequence of the A-loop of rat ErbB2/neu is identical to that of human ErbB2, suggesting it may also undergo a conformational change when the corresponding Tyr882 is phosphorylated.…”
Section: Discussionsupporting
confidence: 79%
“…Tyr882 phosphorylation of the A-loop of rat ErbB2/neu is important for its intrinsic kinase activity (39). We determined whether the analogous Tyr877 is phosphorylated to a higher level in ErbB2-5M than in the wild-type kinase, and we found that it was dramatically increased (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Whereas the significance and functionality of HER2 (Tyr 877 ) phosphorylation is poorly defined (22), phosphorylation of the homologous HER1 (Tyr 845 ) site is nevertheless known to be src mediated (23). Because the homologous site to HER2 (Tyr 877 ) in the activated rat p185 neu protein (HER2 Tyr 882 ) is an autophosphorylation site and mutation of this residue reduces the intrinsic kinase activity of the protein and its transforming potential, this suggests that this tyrosine residue has an important functional role (24). Other phosphorylation sites on HER1 and HER2 were less informative, although the increased phosphorylation status of HER1 (Tyr 1045 ) in OVCAR5 and 41M cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…32 The Y877 residue, for instance, is located in the activation loop of the Her2 kinase domain. Although the role of Y877-Her2-phosphorylation is the subject of debate, 33,34 the Her2 kinase domain has been suggested to be catalytically active only if it is phosphorylated at this regulatory residue. Xu et al 35 reported that autophosphorylation of Y1248 was decreased after mutation of Y877 to phenylalanine and that Y1248 might occur as a result of Y877 phosphorylation.…”
Section: © 2 0 1 2 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%